(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This theoretical paper refers to a methodological model of Body Maps as a strategy to create knowledge on corporeity in bibliographic research. This model approaches the body as a place through which the intersubjective construction path regulating the subject flows, allowing the textualization of subjective processes which, together with the traditional strategies of the bibliographic method, remain invisible as embodied semiotic-material languages. At an interpretational level, the paper deals with understanding the normative order of the body where aspects relative to psychosexual processes and gender models rooted in the culture articulate, along with the expression of transgression to current gender ideologies.